The Art of silence pantomimes with Marcel Marceau, [Group 1] (Chicago Encyclopedia Britannica Educational Corp., 1975)
Features Marcel Marceau in a performance of pantomime.
Contents: Tape 1. Group 1 (27 min.). Pantomime: the language of the heart -- BIB as skater -- The Creation of world -- Tape 2. Group 4 (33 min.) The Dream -- The Maskmaker -- Youth maturity, old age and death -- The Side Show.
Keywords: Marceau, Marcel; Pantomimes